ATTITUDES OF YOUNG PEOPLE IN HEBRON GOVERNORATE TOWARDS SOURCES OF INFORMATION AND NEWS IN THE NEW MEDIA: FACEBOOK AND TWITTER PERSPECTİVE - Abed Al-Qader Mohammad Al-Shrouf; Belal abd elmjeed Khasawneh (American Journals Publishing, 2023)
The study aims to identify the attitudes of young people in Hebron Governorate towards the sources of information and news in the new media (Facebook and Twitter as a model) and to identify The most important cognitive, behavioral, and emotional influences that the new media creates on young people in Hebron Governorate, and the reasons for their interest in it? The analytical descriptive approach was adopted in this study, which describes the phenomenon in an accurate description The study population consisted of young people in the Hebron Governorate, and one of its most prominent questions was whether the youth in the governorate considered the new media as reliable sources in transmitting news, information and ideas? What are the reasons for young people's interest in the new media rather than the traditional media? found that the motives of young people's use of social media reached the highest motive, which is entertainment, at a rate of 76.7%, while the percentage of surfing news websites reached 73.3 %. The emotional effects reached 5%, and the total approval of young people’s trust in popular information on social networking pages amounted to 29.4%. Based on these results, the researcher recommends those in charge of social networking pages to pay attention to the factors that promote young people's use of these means, to pay attention to the contents that they publish constantly, to constantly review the content and content they contain, and to work to make these new media outlets concerned with educating young people in the first place and providing solutions about issues and problems they face.